2022
DOI: 10.1007/s10854-022-07844-3
|View full text |Cite
|
Sign up to set email alerts
|

Optoelectronic and birefringence properties of weakly Mg-doped ZnO thin films prepared by spray pyrolysis

Abstract: Mgx Zn 1−x O thin lms were deposited on glass substrate with x varied between 0.01 and 0.05 by spray pyrolysis at a temperature of 450 °C. The structural investigation showed that all thin lms had ZnO wurtzite structure with a preferred (002) orientation. The gap energy was calculated using Tauc's plot and it decreased over the Mg content by 0.07 eV. The charge carriers' density dropped by an order of 10 5 as Mg content increased whereas the resistivity and the mobility increased. SEM observations revealed a s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 56 publications
(32 reference statements)
1
4
0
Order By: Relevance
“…As seen from Table 3, band gap increased from 3.30 eV to 3.45 eV along with the Mg doping. These values are consistent with the previously reported studies and increment in band gap with increasing amount of doped Mg also reported by others [23][24][25][26][27].…”
Section: ( ) ( )supporting
confidence: 94%
“…As seen from Table 3, band gap increased from 3.30 eV to 3.45 eV along with the Mg doping. These values are consistent with the previously reported studies and increment in band gap with increasing amount of doped Mg also reported by others [23][24][25][26][27].…”
Section: ( ) ( )supporting
confidence: 94%
“…Hexagonal ZnO (wurtzite, JCPDS 36-1451) was used to compare the detected peaks. We have observed from XRD diffraction peaks various diffraction peaks such as (100), (002), and (101) planes, which found by many authors [16][17][18]. In each of the samples, the observations revealed three diffraction peaks, the greatest being at 2θ = 31.6°, 2θ = 34.42°, and 2θ = 36.10°, and matching to the following plans (100), ( 002) and (101), respectively, which are demonstrated by Diha et al [19] and Cao and Bai [20].…”
Section: Resultsmentioning
confidence: 86%
“…As the Mg doping level increased, the absorption region peaks shifted towards shorter wavelengths. The observed blue shift in the optical band gap is directly related to this result [17]. Due to variations in electronegativity and ionic radius differences between Mg and Zn, structural defects that may be created by the substitution of Mg atoms can be linked to an increase in band gap [18].…”
Section: Figure 2 Sem Images Depicting Surface Morphologies Of Mgzno ...mentioning
confidence: 83%
“…The thin films optical bandgap has been calculated using Tauc's relationship given by [22], Taking MgZnO as a direct transition material to consideration, n's value has been defined to be 2 in order to construct the graph of (ߙℎߥ) 2 vs ℎߥ. After that, the optical bandgap of thin films synthesized from varying Mg concentrations of 2, 4, 6, 8, and 10% were estimated to be 4.8, 5.2, 5.3, 5.4 and 5.46eV, Individually, by projecting the linear segment of the non-linear curve until it reaches the x-axis [16,17,21]. It is observed that a higher percentage of MgO atoms get substituted into the ZnO lattice the wider the Eg.…”
Section: Figure 2 Sem Images Depicting Surface Morphologies Of Mgzno ...mentioning
confidence: 99%